The Relationship Between Anxiety Level and Sleep Quality in Hypertensive Patients in the Haemodialysis Unit - Rosida Nur Aisah; Arina Maliya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Haemodialysis patients with hypertension often face complex mental and physical health challenges, including impaired anxiety and sleep quality. This has a profound effect on the individual's life. Objective: This study aims to analyse the relationship between anxiety levels and sleep quality in hypertensive patients undergoing haemodialysis. Quantitative with a cross-sectional approach with a total sampling method of 30 hypertensive patients in the haemodialysis unit of PKU Aisyah Boyolali Hospital. This study was conducted in September - November. The instruments for data collection included the Hamilton Anxiety Rating Scale (HARS) to assess anxiety levels and the Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality. Spearman's test was used for data analysis due to the non-normal distribution of the data. The results of the Spearman statistical test on hypertensive patients in the Hemodialysis Unit of PKU Aisyah Singkil Boyolali Hospital showed a p value = 0.044 > α = 0.05. the main findings (past tense). The results showed a significant relationship between anxiety levels and sleep quality in hypertensive patients at the Hemodialysis Unit of PKU Aisyah Singkil Boyolali Hospital. Researchers suggest examining other variables that affect sleep quality, such as physical activity, diet, and adherence to medication. Qualitative research methods can also be employed to investigate the personal experiences of patients and a broader range of individuals, allowing for more generalized findings.